Analisis Faktor Perilaku Seks Pranikah Remaja Berdasarkan Teori Transcultural Nursing di Kabupaten Sumba Timur - Imelda Mbati Mbana; esti yunitasari; ni ketut alit armini (Universitas Airlangga, 2019)
Introduction: Adolescent sex behavior is strongly influenced by several things related to the theory of transcultural nursing. The high teenage sex behavior has an impact on the high rate of unwanted pregnancies, maternal mortality and infant mortality and various other health problems. This study aims to analyze transcultural nursing factors related to premarital sexual behavior of adolescents in East Sumba Regency.Methods: The design of this study is descriptive analytical with a cross-sectional approach. The sample was selected by simple random sampling, namely students of class X and XI SMA N 1 Lewa and SMA N 1Nggaha Ori Angu. Data retrieval using questionnaire instruments as many as 6 instruments that have been tested for validity and reliability by researchers and the results of the study were analyzed using the chi square-Pearson test.Results: The high rate of premarital sexual behavior of adolescents in East Sumba Regency was related to social factors and kinship (p = 0.004), culture and lifestyle (p = 0.011), and economy (p = 0.004). Premarital sex behavior is not related to technological factors (p = 0.292), policy and regulations (p = 0.775) and education factors (p = 0.890).Conclusion: There was 3 variables related to premarital sex, namely social factors and kinship, culture and lifestyle and economy. This is due to the existence of local cultural customs and customs which allow arranged marriage in adolescents. Matchmaking is carried out by parents with the aim of completing the social strata (maramba) and mostly to improve the economic status of the family.